Superficial-Temporal-Artery-To-Middle-Cerebral-Artery Bypass in Cerebrovascular Occlusive Disease and Hemodynamic-Related Ischemia: Illustrative Case and Literature Review - Isolan, Gustavo Rassier; Caracante, Ricardo de Andrade; Telles, João Paulo Mota; Rabelo, Nícollas Nunes; Figueredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Stroke is the third most common cause of death worldwide. About 10% to 15% of strokes related to the territory of the carotid artery are associated with its complete occlusion. There is an important subgroup of patients with cerebrovascular occlusive diseases who might benefit from an external-carotid-to-internal-carotid bypass. In the present study, we report a case of a 53-year-old male patient with stenosis of the M2 branch of the middle cerebral artery (MCA), with a history of ∼ 20 episodes of transient ischemic accidents (TIA)s, in whom an anastomosis of the M4 branch of the superficial temporal artery-MCA was performed. The patient was discharged in three days, and in the two years of follow-up, they were no more TIAs. We also conducted a review of the literature on cerebrovascular occlusive disease and extracranial-intracranial bypass surgery. New methods to evaluate cerebral hemodynamics made it possible to classify a new subgroup of patients with symptomatic cerebrovascular disease and documented cerebrovascular compromise in whom the drug therapy fails, who can benefit from the extracranial-intracranial bypass. Our case report illustrates the advantages of revascularization in these selected patients.
Keywords: extracranial-intracranial bypass; middle cerebral artery; superficial temporal artery; microvascular anastomosis; cerebrovascular occlusive disease